Pengaruh Investasi Sektor Perikanan Terhadap Perekonomian Indonesia - Agustina Arida (Jurnal Penelitian Agrisamudra, 2019)
Fisheries sub-sector in Indonesia has long maintained as the support of the nation's economy. Increased investment fisheries sub-sector has encouraged the acceleration of development in this sector, due to a positive impact on the structure of production, the availability and accessibility of capital, technology and the availability of skilled labor, which it is a component of the development of Indonesia's economic growth rate. The aim of research to determine the effect of increased investment toward increased revenues, and the influence of economic growth on investment. The model is made in the form of simultaneous equations, then estimated using 2SLS (two stage least square). Prior to estimation, to identify whether the equation which will direduce form has been identified or over-identified. The results of the agricultural sub-sector investment research has not been a significant impact on economic growth in Indonesia. Cases in Indonesia, economic growth or an increase in the national income will have an effect on the growth of investment. This is consistent with the theoretical aspects of these two variables, which, if income increases, the investment will also increase. Woke up only one-sided relationship, in this case affects only GDP but investment sub Investment agricultural sector has not been much (not significant) role in improving economic growth in Indonesia.